Competences in health promotion in multiprofessional residence: recognizing domains and knowledge of professionals (Research, Society and Development, 2022)
Objective: to understand the knowledge of professionals linked to the multiprofessional residency on competencies in health promotion. Method: qualitative study anchored in the theoretical framework Developing Competencies and Professional Standards for Health Promotion Capacity Building in Europe (CompHP), carried out from a semi-structured interview with 16 resistant individuals from a Multiprofessional Residency Program. Data were transcribed and organized based on thematic analysis. Results: two categories emerged from the speeches, the first indicates that the residents present conceptions about competences and competences in health promotion, either as an articulation of knowledge, skills and attitudes, or as specific professional attributions of the training nucleus, and the second, presents the domains of competences in health promotion of the CompHP manifested in the informed practices of the residents. Conclusion: There is an advance in the understanding of skills and competences in health promotion, although there is still confusion regarding the applicability of the term, mainly related to its polysemy.